A Comparative Study of Novel Topologies of Magnetic Gears - Shuangxia Niu; Yuan Mao (Energies, 2016)
The magnetic gear (MG) is an emerging technology that has been proved to possess superior performance over the conventional mechanical gear in many aspects. However, the existing markets of traditional mechanical gears have not yet been replaced by MGs. One of the major reasons is that MGs are susceptible to the permanent magnet (PM) materials, which are scarce and expensive, while mechanical counterparts are impervious to that. To solve such issues, the comparative studies of various designs of triple-layer PM-excited MGs are carried out to find out the optimal torque per unit PM volume design. The methodology of the Tabu algorithm is coupled with the finite element method (FEM) to search out the optimal solution of MGs.